High-Q On-chip Passive Components and Low-Phase-Noise CMOS Bridge Oscillator Design - Shuvra, Shaeera Rabbanee (University of Waterloo, 2024)
High-Q passives are the key design components for a proposed resonator circuit. This thesis focuses on designing and optimizing passive components (transmission lines, capacitors, and inductors) implemented in a production 22-nm SOI-CMOS technology. Custom-designed inductors with inductances of 1 nH and 2 nH are employed, achieving quality factors (Q) greater than 30 at 10 GHz. These inductors are realized through the utilization of BEOL Stack 11 and Stack 19 configurations in the 22-nm technology with varying shielding patterns. Additionally, high-Q capacitors are implemented exhibiting Q factors surpassing 500 at 10 GHz, and an operational range validated by measurements up to 60 GHz. Balanced transmission lines with Q factor greater than 150 at 25 GHz are also designed and implemented. This high-Q value is explained with a new lumped-element equivalent circuit model developed in this work.   A state-of-the-art, fully-integrated bridge resonator with a quality factor (Q) exceeding 50 at 8.5 GHz is introduced in this thesis. This level of performance is realized through circuit design techniques and the integration of the custom inductor and capacitor designs. Furthermore, the potential for application of this high-Q bridge resonator in the design of a low-phase-noise RF oscillator is demonstrated, with post-layout simulations predicting a phase noise below -131 dBc/Hz at 1 MHz offset for 8-GHz carrier frequency.
Keywords: RF circuits; oscillator; high-Q passives; bridge resonator; phase noise